2017
DOI: 10.1016/j.jpainsymman.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed and Survival in Patients With Brain Metastases

Abstract: Gait speed is associated with overall survival in patients with newly diagnosed brain metastases. Gait speed assessment is simple, objective, and may provide additional prognostic information to improve life expectancy estimation and management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…Similar to our results, a previous multinational study performed a pooled analysis of nine cohorts, finding that gait speed was a risk factor for mortality, independently of confounders [37]. Likewise, other studies have evaluated the survival of older adults with cancer who had slow gait speed, but only included patients with brain and hematological cancer, respectively [11,38]. This is important to take into account since while the incidence of these types of cancer is not high, the mortality is [2], and thus, these studies reported a greater magnitude of association.…”
Section: Comparison With Literaturesupporting
confidence: 87%
“…Similar to our results, a previous multinational study performed a pooled analysis of nine cohorts, finding that gait speed was a risk factor for mortality, independently of confounders [37]. Likewise, other studies have evaluated the survival of older adults with cancer who had slow gait speed, but only included patients with brain and hematological cancer, respectively [11,38]. This is important to take into account since while the incidence of these types of cancer is not high, the mortality is [2], and thus, these studies reported a greater magnitude of association.…”
Section: Comparison With Literaturesupporting
confidence: 87%
“…The third level of performance assessed, independent standing, greatly increases participation in ADL [ 23 , 56 ], and the fourth level of motor skill, independent gait, not only determines participation in an active life and provides a sense of self-confidence but is also important for social and mental health. Gait efficiency, especially speed of gait, is a known survival factor in patients with brain tumors [ 57 ]. We found that gait efficiency was worst in the VS group, both before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At discharge, the condition of patients in both groups significantly improved relative to the scores after surgery but did not return to preoperative levels. Other authors have emphasized the effectiveness of postoperative rehabilitation as well as the need to continue rehabilitation in the post-hospital period [ 24 , 34 , 43 , 59 , 67 , 71 , 72 , 73 , 74 ]. Despite improvements, only half of the repeat surgery group were able to walk independently, as assessed by the GI scale, while in the first surgery group, 60.2% of participants were able to walk independently with orthopedic aids.…”
Section: Discussionmentioning
confidence: 99%
“…Independent gait not only determines participation in an active life but also provides a sense of self-confidence important for social and mental health. Speed of gait is a known survival factor in patients with brain tumors [ 72 ]. Average LOS values did not differ significantly between groups 18 days in the repeat surgery group and 16.5 days in the first surgery group, over three times longer than LOS after surgery in patients not requiring rehabilitation (5.1 days) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%